Factors Affecting in-stent Restenosis in Patients Undergoing Percutaneous Coronary Angioplasty: - Sajadian, Mostafa; Alizadeh, Ladan; Ganjifard, Mahmoud; Mardani, Armin; Ansari, Mohammad Ali; Falsoleiman, Homa (Galen Medical Journal, 2018)
Percutaneous coronary angioplasty (PCI) and stent implantation are the most common therapeutic strategies for coronary artery stenosis; however, in-stent restenosis (ISR) is one of its important challenges. Although in some studies, coronary artery disease (CAD) factors are deemed to be the causes of ISR, in some others, the relationship between CAD factors and ISR are not observed. Over the past ten years, there has been no review article on factors affecting the ISR. This article aimed to review the possible factors affecting ISR in patients undergoing PCI. This narrative review study was conducted on PubMed, Web of Science, Scopus, and Google Scholar databases between 1 January 1990 and 30 July 2017. After initial screening of 1728 retrieved articles, 1401 articles were excluded to due irrelevancy to the review; and finally, 39 papers were selected for data collection. Our study results showed that the site and length of implanted stent, hypertension and diabetes are the most probable factors affecting ISR. Further studies are required for evaluation of the effect of other possible risk factors such as genetic sequencing, obesity, chronic infections and hemoglobin A1C levels. [GMJ.2018;7:e961] Â 